Cross-Country Analysis of Funding Models of Medical Organizations in the Context of the COVID-19 Pandemic - S. S. Budarin; D. O. Vatolin; Iu. V. Elbek (Vestnik MGIMO-Universiteta)
Abstract: The COVID-19 coronavirus infection has made significant adjustments to the management of the health care system, both in Russia and abroad. Different models of financing health systems in different ways responded to the management in emergency situations. According to experts, systems with a state-based socially oriented model of health care were more effective. At the same time, opinions were divided on the effectiveness of the insurance model for financing medical organizations that provide different types of medical care to the population. The article analyzes measures to provide medical organizations with financial and material and technical resources in countries with different economic models of the health system, and on the example of outpatient clinics in Moscow, compares changes in the main financial indicators in the first half of 2020 and assesses the financial stability of medical organizations during the period of restrictions on preventing the spread of COVID-19 coronavirus infection. The hypothesisis that financial condition of polyclinics during the period of restrictions has improved. It is based on the assumption that declining number of visits to medical organizations reduces the level of organizations’ expenditures while maintaining the volume of their income at almost the same level due to the principle of per capita state financing of medical organizations that provide outpatient medical care. Based on the results of the analysis, it is concluded that the financial stability of adult polyclinics is maintained and the financial stability of children's polyclinics is increased.